Acetylcholine in the gingival epithelium drives the pathogenesis of periodontitis - Xu, Shihan; Guo, Jiaxin; Yang, Shiwen; Cheng, Bin; Xia, Juan (Frontiers in Cell and Developmental Biology, 2025)
BackgroundPeriodontitis is a highly prevalent chronic inflammatory disease characterized by the progressive destruction of periodontal tissues, which can lead to tooth loss and affect systemic health. This pathological process is driven by both epithelial barrier disruption and a self-perpetuating cycle of dysregulated inflammatory immune responses. Although neurotransmitters, including acetylcholine, are abundant in saliva and gingival crevicular fluid, their role as key mediators of immune homeostasis in the pathogenesis of periodontitis remains poorly understood.MethodsUtilizing single-cell RNA sequencing (scRNA-seq) data (205,334 cells, 40 human gingival samples) and gingival spatial transcriptomics data (46,230–25 μm2 spots), we revealed that the gingival epithelium exhibits the most significant functional reprogramming of neural signaling pathways in the periodontitis state. Through experiments in vivo and in vitro, we validated the functional role of acetylcholine in periodontitis.ResultsOur findings reveal that cholinergic signals change with the progression of periodontitis and that gingival epithelial cells possess an extensive distribution of non-α7-type nicotinic receptors. The acetylcholine-degrading enzyme, acetylcholinesterase (AChE), is primarily expressed by myeloid immune cells that extensively infiltrate the epithelium, and its expression is significantly upregulated following periodontal treatment. In human oral keratinocytes (HOKs), acetylcholine played a dual role: it promoted epithelial barrier repair by reversing Porphyromonas gingivalis (P. gingivalis)-induced tight junction disruption, yet it also exacerbated inflammation by upregulating key chemokines and inflammasome components. In vivo, mouse models of periodontitis showed that topical application of acetylcholine aggravated periodontal tissue damage.ConclusionIn conclusion, our results reveal a complex, multifaceted role for acetylcholine in periodontal pathogenesis, highlighting its ability to both protect the epithelial barrier and drive inflammatory tissue destruction. These findings establish a new “neuro-epithelial-immune axis” in the pathogenesis of periodontal disease and reveal potential targets for therapeutic intervention.